The to-day and to-morrow reader
1 online resource (vii, 421 pages)
Keywords: "The To-day and To-morrow book series (1923-31) was a unique publishing phenomenon--over 100 short, often brilliant, books choosing a particular subject, outlining its present state, and then speculating about its future. This Reader brings together some of the best work in the series, including eleven complete volumes and substantial extracts from ten more. To-day and To-morrow is one of the key documents of modernity. It contains some of the best writing of the twentieth century, and some of the most visionary predictions. The contributors were creative writers, scientists, inventors, philosophers, lawyers, doctors and teachers. Included here are Bertrand Russell, Vera Brittain, Sarvepalli Radhakrishnan, Robert Graves and the scientists J.B.S. Haldane, J.D. Bernal, and Sir James Jeans. The topics range from emerging technologies such as the talkies, television, robotics and drones, to speculations about future technologies like test-tube babies, artificial wombs, cyborgs, genetic modification, hormone replacement therapy, space exploration, the internet, and the possibility of hive minds. The books consider how societies will respond to such developments; how the transformations will impact on lives, relationships, beliefs, politics. To-day and To-morrow brings new perspectives to the literature and culture of modernism and modernity for general readers, students and scholars. It sheds new light on twentieth-century literature, culture and society. It offers resources for teachers and students of creative writing--and everyone--facing the challenge of thinking about our future"--